The study of the psychological characteristics of the pharmacist's personality in the aspect of the corporate culture of the pharmacy organization - N. A. Rodina; O. P. Kashina; M. A. Zhegalova (Вестник университета)
The article presents the results of a study of the pharmacist's personality in the context of corporate culture, on the basis of which a comprehensive program for the development of the personal potential of employees of pharmacy organizations was developed. The sample consisted of 70 specialists (pharmacists) working in pharmacy chains in the city of Nizhny Novgorod. The results of the study indicated significant changes that occurred in the experimental and control groups according to all the analysed criteria. The significance of the results obtained for science is to expand the understanding of the multidimensional personality qualities of pharmacists required by representatives of this profession, which allows us to study this phenomenon in more detail, to explain some features of the personality of pharmacists, on whose professionalism depends the quality of the work performed, and hence the health of society.